Exploring the Motives of Young Audience for Theatre Attendance (Vallis Aurea, 2020)
This paper presents scientific research at the national level in the Republic of Croatia, i.e. the analysis of the motives for the arrival of the younger age group, the generation Y so-called millennials and generation Z's in city and national theatres. The institutions of culture in the Republic of Croatia are always trying to find the best way to contain existing and attract new audiences. The aim of this paper is to investigate the development of young theatre audiences, i.e. their motives, but also the obstacles of attendance in to city and national theatres.